The Future of Medical Technology: Recent Innovations in Artificial Intelligence and Robotics for More Precise and Efficient Treatment - Farah, Rina; Nizam, Zain (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
The rapid advancement of artificial intelligence (AI) and robotics has transformed the landscape of medical technology, offering unprecedented precision, efficiency, and personalization in patient care. The integration of AI-driven diagnostics and robotic-assisted surgery has improved clinical decision-making, minimized human errors, and enhanced surgical outcomes. This study aims to explore recent innovations in AI and robotics in the medical field, assess their effectiveness in improving treatment precision, and identify challenges in their widespread adoption. A systematic review methodology was employed, analyzing recent peer-reviewed articles, case studies, and reports from medical institutions and technology developers. The findings indicate that AI-powered diagnostic tools significantly enhance early disease detection, while robotic surgery enables minimally invasive procedures with improved accuracy and reduced recovery times. However, challenges such as ethical concerns, high implementation costs, and regulatory hurdles remain key barriers to full-scale adoption. This study concludes that AI and robotics will play an increasingly vital role in modern medicine, revolutionizing healthcare delivery. Further research should focus on optimizing AI algorithms, addressing ethical considerations, and developing cost-effective solutions to ensure broader accessibility and acceptance in medical practice.